2018
DOI: 10.3389/fmicb.2018.01234
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Interactions With Dissolved Organic Matter Drive Carbon Dynamics and Community Succession

Abstract: Knowledge of dynamic interactions between natural organic matter (NOM) and microbial communities is critical not only to delineate the routes of NOM degradation/transformation and carbon (C) fluxes, but also to understand microbial community evolution and succession in ecosystems. Yet, these processes in subsurface environments are usually studied independently, and a comprehensive view has been elusive thus far. In this study, we fed sediment-derived dissolved organic matter (DOM) to groundwater microbes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 75 publications
10
115
2
1
Order By: Relevance
“…(2) Stimulation of the autochthonous bacterial community in response to influx of diverse DOM substrate from the surface (Zhang et al, 2015;Rajala and Bomberg, 2017;Wu et al, 2018). The two potential drivers are not mutually exclusive and could have a combined effect.…”
Section: Responses Of the In Situ Biospherementioning
confidence: 99%
See 1 more Smart Citation
“…(2) Stimulation of the autochthonous bacterial community in response to influx of diverse DOM substrate from the surface (Zhang et al, 2015;Rajala and Bomberg, 2017;Wu et al, 2018). The two potential drivers are not mutually exclusive and could have a combined effect.…”
Section: Responses Of the In Situ Biospherementioning
confidence: 99%
“…Specifically, the predominance of microorganismderived proteins and lipids are expected during the recession periods (Kallenbach et al, 2016;Kujawinski et al, 2016;Ding et al, 2018). Furthermore, the interactions of microorganisms with DOM can drive community succession (Li et al, 2013;Zhang et al, 2015;Wu et al, 2018). Previous investigations have indicated that aquifer-surface connection and recharge events are reflected in bacterial diversity and bacterial community composition (Kolehmainen et al, 2007;Li et al, 2012;Cooper et al, 2016;Hubalek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that spatially heterogeneous molecular species in rainwater are converted into spatially homogeneous ones during the process where rainwater passes through the tree canopy of the conifer plantation and thereby dissolves and leaches plant-derived molecular species. Proteins are relatively labile and biodegradable compounds [37]. Given that the DOC flux and the number of proteins were much higher in throughfall than in rainfall, the spatially homogenized quality of throughfall water supports the indication of Qualls and Haines [10] that tree leaves leach readily-mineralisable DOM to the rainwater, which in turn can stimulate microbial activities in the forest floor.…”
Section: Discussionmentioning
confidence: 77%
“…The small organic C only enriched a few phyla which are commonly isolated and already have diverse representative isolates (Figure 2). As the major naturally occurring C sources for microbes in the subsurface, sediment NOM are mixtures of heterogeneous organic substrates containing proteins, nucleic acids, lipids, carbohydrates, etc 41 . These undefined complex C support various subsurface bacteria in culture medium under laboratory condition, which may benefit for cultivation and isolation of key bacteria species from subsurface environment.…”
Section: Discussionmentioning
confidence: 99%
“…The sediment sample for NOM extraction was collected from a background well FW305 at ORR-FRC, at the depth of 0.3-1.1 m below ground surface. The potential bioavailable fraction of sediment NOM was extracted according to the method previously developed in our lab 28 . Briefly, the freeze-dried sediment sample was extracted with Milli-Q water via rotary shaking (170 rpm) overnight at 35 °C, and then sonicated in water bath for 2 hrs.…”
Section: Methodsmentioning
confidence: 99%